Therapeutic potential of Garlic (Allium sativum L.) on new models of asthma immune pathobiology: A review - VR Bataduwaarachchi; DCJ Liyanage; SMN Hansanie; HDSM Perera; LG D'Cruz (Phytomedicine Plus)
Background: Asthma, a prevalent chronic immune-mediated respiratory disease, has long been a global health concern. In this context, the potential of garlic (Allium sativum L.) to modulate the immune pathobiology of asthma is of great interest. However, the molecular and immune-mediated effects of garlic remain inadequately explored in the context of emerging asthma pathobiological models. Aims of the study: This review aims to explore the potential effects of garlic (Allium sativum L.) on the immune pathobiology of new asthma models and to provide guidance and comprehensive reference material for preclinical and clinical studies. Materials and methods: A comprehensive literature review was conducted in PubMed, Medline Scopus, and Google Scholar. A combined search was performed for each keyword, with “garlic” included as the primary keyword or search term. Articles were included if they primarily focused on the effects of garlic compounds on the immune pathobiology of asthma. Results: The administration of s-allyl-cysteine mercapto-l-cysteine (SAC) suppresses inflammatory events in asthma by specifically downregulating TH2 cytokines. It also reduces vital key proinflammatory mediators, including IL-6, PGE2, and COX2, which are vital in asthma pathogenesis. Garlic (Allium sativum L.) compounds further suppress inflammatory response via modulation of NF-κB/IκB expression. Additionally, sulphur compounds inhibit the activation of NLRP3 inflammasome, via the suppression of asthmatic inflammatory response. Conclusion: The garlic (Allium sativum L.) compounds, including SAC, potentially show multiple biological functions, including specific effects on TH2 inflammation and other immune-modulatory and antioxidant properties against specific immune-mediated asthma pathobiological pathways.